Uji Aktivitas Antibakteri Fraksinasi Alkaloid Ekstrak Kulit Kayu Raru (Cotylelobium melanoxylon Pierre) Terhadap Bakteri Escherichia coli dan Staphylococcus aureus - Salwa, Shakhila; Daulay , Anny Sartika; Rahayu , Yayuk Putri; Ridwanto, Ridwanto (Journal of Pharmaceutical and Sciences, 2025)
Background: Indonesia is rich in medicinal plants, including Cotylelobium melanoxylon Pierre (raru bark), traditionally used to treat diarrhea, malaria, and diabetes. However, scientific validation of its alkaloid compounds and antibacterial potential is still limited. Objective: This study aimed to (1) fractionate alkaloids from raru bark extract using chloroform liquid-liquid extraction, (2) identify alkaloid functional groups via FT-IR spectroscopy, (3) quantify alkaloid levels in ethanol and methanol extracts using UV spectrophotometry, and (4) evaluate their antibacterial activity against Escherichia coli and Staphylococcus aureus. Methods: The research stages included plant material processing, ethanol/methanol extraction, phytochemical screening, alkaloid fractionation with chloroform, FT-IR analysis, UV spectrophotometry for alkaloid quantification, and antibacterial testing via disc diffusion at 40%, 50%, and 60% concentrations. Results: Alkaloid fractions were successfully isolated, containing functional groups N-H, C-N, C=O, aromatic C=C, and sharp C=O. The methanol extract yielded higher alkaloid levels (21.03 ± 0.10%) than ethanol (18.95 ± 0.09%). The 50% alkaloid fraction showed the strongest antibacterial activity, with inhibition zones of 21.1 mm (E. coli) and 23.1 mm (S. aureus). Conclusion: Raru bark alkaloids exhibit significant antibacterial effects, with methanol extract demonstrating superior alkaloid content and efficacy.